Zooplankton and micronekton active flux around the Iberian Peninsula - Couret, María; Sarmiento-Lezcano, Airam N.; Landeira, José María; Giering, Sarah L. C.; Major, Will; Olivar, M. Pilar; Díaz-Pérez, Javier; Castellón, Arturo; Hernández-León, Santiago (Frontiers in Marine Science, 2025)
The biological carbon pump comprises a set of processes that transfer organic carbon from the ocean surface to its depths, playing a vital role in the global carbon cycle. Estimating the amount of carbon transported by this pump remains challenging due to the complex, variable nature of its pathways and the limited availability of comprehensive measurements. While the contribution of zooplankton to active flux has been examined, with studies reporting 10-30% of total particle export, the role of micronekton in this process is still poorly understood. Furthermore, the relative capacity of both communities to export carbon remains largely unclear. Here, we report total (zooplankton plus micronekton) active and passive fluxes from the Mediterranean Sea to the Atlantic Ocean around the Iberian Peninsula, to explore how total active flux is influenced by environmental conditions. Water column physical properties differed between the Mediterranean and Atlantic Ocean zones, with chlorophyll a values two-fold higher in the upwelling off Portugal. Particulate organic carbon fluxes from sediment traps ranged from 4.24 ± 0.2 to 7.94 ± 3.9 mg C·m-2·d-1. Active flux was dominated by zooplankton in the Mediterranean Sea (77.2 ± 21.2 vs. 14.8 ± 3.4 mg C·m-2·d-1 in the Atlantic), whereas micronekton contributed more in the Atlantic Ocean (15.1 ± 9.4 vs. 7.9 ± 6.8 mg C·m-2·d-1). This pattern shows that active flux far exceeded passive flux in all regions, with pelagic decapods playing a particularly important role in the northern Atlantic. Our results highlight the ecological significance of both zooplankton and micronekton in driving carbon flux, underlining the need to understand their relative contributions across contrasting environments to better explain the functioning of the biological carbon pump.